Au nanoparticle-based sensor for apomorphine detection in plasma - Zanchi, Chiara; Lucotti, Andrea; Tommasini, Matteo; Trusso, Sebastiano; de Grazia, Ugo; Ciusani, Emilio; Ossi, Paolo M. (Beilstein Journal of Nanotechnology, 2015)
Artificially roughened gold surfaces with controlled nanostructure produced by pulsed laser deposition have been investigated as sensors for apomorphine detection aiming at clinical application. The use of such gold surfaces has been optimized using aqueous solutions of apomorphine in the concentration range between 3.3 × 10−4 M and 3.3 × 10−7 M. The experimental parameters have been investigated and the dynamic concentration range of the sensor has been assessed by the selection of two apomorphine surface enhanced Raman scattering (SERS) peaks. The sensor behavior used to detect apomorphine in unfiltered human blood plasma is presented and discussed.
Keywords: apomorphine; Au NPs; nano-roughened films; pulsed laser deposition; self-assembled films; SERS